Perancangan User Interface dan User Experience Website KosIN dengan Pendekatan Design Thinking - Ida Bagus Ari Widhiana; Luh Gede Astuti (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
The need for education or employment drives people to move to other areas that offer greater access to education or job opportunities. Individuals who move to a new area for higher education or job search often face challenges in finding accommodations that meet their needs. The increasing number of newcomers has led to a growing demand for housing. The main constraint is that individuals must physically go to the location to search for accommodations like boarding houses (